NanoSQUIDs based on niobium nitride films. (29th December 2016) - Russo, R; Esposito, E; Crescitelli, A; Di Gennaro, E; Granata, C; Vettoliere, A; Cristiano, R; Lisitskiy, M
Abstract: We present an experimental investigation of nanoSQUIDs based on niobium nitride films. Niobium nitride has a relatively high critical temperature and a large upper critical magnetic field, making it a good material for superconducting electronics working in high magnetic field. We have fabricated nanoSQUIDs using electron beam lithography lift-off technique and deposition of niobium nitride films by magnetron sputtering at room temperature. The characterization of nanoSQUIDs was performed at 4.2 K and it consists mainly of current–voltage ( IV ) characteristics and critical current as a function of external magnetic field (magnetic pattern). The fabricated nanoSQUIDs show a hysteretic IV characteristic and they present a multi-values magnetic pattern. We show that by reducing the critical current by ion etching it is possible to obtain nanoSQUIDs with a single value magnetic pattern suitable for magnetic particle measurements. Magnetic noise analysis has been performed and a white noise of 0.3 μ Φ0 Hz −1/2 has been estimated.